Validation of the EULAR/ERA-EDTA recommendations for the management of ANCA-associated vasculitis by disease content experts - Yates, Max; Watts, Richard; Bajema, Ingeborg; Cid, Maria; Crestani, Bruno; Hauser, Thomas; Hellmich, Bernhard; Holle, Julia; Laudien, Martin; Little, Mark A; Luqmani, Raashid Ahmed; Mahr, Alfred; et al. (RMD open, 2017)
The European League Against Rheumatism recommendations for the management of antineutrophil cytoplasmic antibody-associated vasculitis have been recently published. Unique to recommendation development, they were also voted on by members of a learned society. This paper explores the wider validity of the recommendations among people who self-identify as clinicians caring for patients with vasculitis. In addition to the task force, a learned society (European Vasculitis Society-EUVAS) was invited, through online survey, to rate independently the strength of evidence of each recommendation to obtain an indication of the agreement among the final target audience and ultimate end-users of the recommendations. The survey took place in June 2015. Of the 158 EUVAS members surveyed, there were 88 responses (55.7%). There was a large degree of agreement in the voting patterns between EUVAS survey participants and task force members. Notable exceptions were lower grades for the recommendation of the use of rituximab for remission induction in patients with eosinophilic granulomatosis with polyangiitis and for methotrexate and mycophenolate mofetil as remission maintenance agents in patients with granulomatosis with polyangiitis/microscopic polyangiitis by EUVAS members. These results are encouraging and suggest that the voting patterns of the task force are representative of the wider vasculitis community. We recommend future recommendations adopt this approach for data/expert-based treatment guidelines, especially for multisystem diseases.